Improving effect of disaccharides and maltodextrin on preparation of egg yolk powder by microwave-assisted freeze-drying: Functional properties, structural properties, and retention rate of active IgY. (15th March 2023) - Wang, Zhe; Duan, Xu; Ren, Guangyue; Guo, Jingfang; Ji, Jiangtao; Xu, Yiming; Cao, Weiwei; Li, Linlin; Zhao, Mengyue; Ang, Yuan; Jin, Xin; Bhandari, Bhesh; et al.
Highlights: Lyophilization can induce the change of lipoprotein structure in egg yolk. Lipoprotein aggregation results in decreased solubility of egg yolk powder. The content of active IgY in yolk decreased after lyophilization. Excipients can improve the properties of lyophilized egg yolk powder. Abstract: The preparation of egg yolk powder (EYP) with excellent solubility and high retention of active IgY is of great significance for increasing the added value and promoting the application of EYP. A new method of preparing EYP by microwave-assisted freeze-drying (MFD) was researched. Confocal laser scanning microscopy results demonstrated that the supplementation of excipients (sucrose, trehalose, and maltodextrin) could inhibit lipoproteins aggregation in egg yolk induced by freezing. Scanning electron microscopy indicated that drying further damaged the structure of lipoproteins in EYP, leading to lipid separation from it. FTIR and fluorescence spectra confirmed this finding, indicating that excipients enhance protein stability. Compared with conventional freeze-drying (FD), EYP prepared by MFD, particularly that containing excipients, had higher solubility (63 g/100 g), active antibody retention rate and shorter drying time. Therefore, excipients can significantly improve the solubility and stability of EYP and the retention rate of active IgY.